Disseminating cervical cancer knowledge : impact of a public seminar. - Parhizkar, Saadat; Abd Latiff, Latiffah; Afshari, Mojgan (Macrothink Institute, 2013)

(untitled)
Cervical cancer is the second most common cancer after breast cancer among women in Malaysia. Cervical cancer screening using Pap smear provides an appropriate way for early detection and prevention of cervical cancer if appropriately implemented. Knowledge and attitudes toward disease and illness have been shown to influence cervical cancer screening in populations. This study was carried out to evaluate the immediate effects of an educational intervention through a scientific seminar on short-term knowledge acquisition. A quasi-experimental pre-test / post-test design was used to assess the efficacy of the public seminar on cervical cancer awareness among Malaysian women. A public seminar was organized by Faculty of Medicine and Health Science University Putra Malaysia. This public seminar focused on how Cervical Cancer Screening can be more accepted by most women in Malaysia and many other Asian and Middle East countries. Data were gathered via a self-administered questionnaire as pre-test. Immediately after delivering speeches by keynote speakers; post-test was carried out. The finding revealed that correct responses increased from 39% (pre seminar) to 71% (post seminar) and there was a significant difference in means scores of knowledge and attitude in pre-test and post-test (P < 0.001). An educational intervention had a positive effect on short-term knowledge and awareness of cervical cancer in Malaysian women. Additional research is necessary to assess long-term retention of information and what effect, if any, increased knowledge has on health behaviour.